Retinol-vezujući protein 4 nivoa odnosi se na prisustvo i težinu bolesti koronarnih arterija: RBP-4 and coronary artery disease - Nar, Gokay; Cetin Sanlialp, Sara; nar, rukiye (Journal of Medical Biochemistry, 2021)
Background: The prevous studies has showed that serum retinol binding protein 4 (RBP4) levels increased in metobolic disorders which are closely associated with cardiovascular dieases (CVD). However the human studies investigating the role of RBP4 in CVD are conflicted. Therefore, we aimed to evaluate the relationship between RBP4 and the presence and the severity of coronary artery disease (CAD) in this study. Methods: 55 patients with presenting acute coronary syndrome (ACS) and 43 control subjects who had various cardiovascular risk factors with normal coronary artery on coronary angiography were included in this study.The serum RBP4 concentrations were measured using ELISA method and clinically and anatomically score models were used to asses the severity of coronary lesion. Results: Serum RBP4 level was significantly higher in patients with ACS compared to the controls (68.40 ± 47.94 mg/L vs. 49.46 ± 13.64 mg/L; p = 0.014). RBP4 was correlated with GENSINI and SYNTAX I score (r = 0,286 p=0,034; r = 0.403 p = 0.002 respectively). However, there was no relationship between RBP4 and GRACE score. Conclusion: Patients with ACS had increased serum RBP4 levels and its high levels were correlated with CAD severity.